Who Is, and Who Is Not a Pagan?: Struggles in Defining Contemporary Paganism: A Response to Ethan Doyle White - Horák, Pavel (The pomegranate, 2020)
The article deals with Pagan studies’ attempts to define contemporary Paganism and claims that definition-building is not a fruitful way of getting to a better understanding of the phenomenon. The article (i) introduces the ways that Pagan studies have tacked the issue of defining contemporary Paganism, (ii) providing particular examples, and (iii) scrutinizing them with a help of classificatory and referential optics. Some scholars in the field have suggested employing family resemblance and polythetic definition for solving the definitional issues. The article (iv) analyzes these propositions and argues why these proposals are not feasible ways of conducting the inquiry. Instead, (v) it proposes a completely different research approach: to formulate a hypothesis, pick a point of reference of contemporary Paganism and test its self-representation against the hypothesis, together with scrutinizing the history of Paganism conceptualizations during the centuries to find out how much these conceptualizations influence our present inquiries and insider self-representations.